Environmental DNA Application to Identify Protozoan Community in the Sediment of Balekambang Lake, Dieng, Central Java - Shafa Tasya Nabila; Tri Retnaningsih Soeprobowati; Ni Kadek Dita Cahyani; Jumari Jumari; Riche Hariyati; Henk Heijnis (Indonesian Journal of Limnology, 2024)
Lake Balekambang, Dieng, has a high level of sedimentation that can affect water quality, so it is necessary to identify organisms to assess the lake's environmental conditions. The use of eDNA methods in Indonesia is minimal, especially in the Dieng area. This research aims to identify the protozoan communities in sediment samples from Lake Balekambang using the Environmental DNA (eDNA) method to assess the lake ecosystem. This study targeting the 18S rRNA gene for single cell eukaryotes. Data analysis was performed using GALAXY and RStudio. Bioinformatics analysis obtained 51,172 reads divided into 48 Amplicon Sequence Variants (ASVs). All specimens were identified as eukaryotes. Protozoa taxa that can be identified are Tritrichomonadidae, Ophryoscolecidae, Gregarinidae, Cyrtolophosididae, Hexamitidae, Isotrichidae, Oxytrichidae, Vannellidae, Vermamoebidae, and other unidentified Eukaryota taxa. Using the eDNA method this study able to identify the protozoan community found in the sediments of Lake Balekambang, Dieng. Protozoa taxa that are identified are taxa that generally inhabit the rumen of ruminants and the gastrointestinal tract of rodents, and are generally pathogens that can cause disease in humans and animals. New knowledge about Environmental DNA Metabarcoding (eDNA) can support research in identifying organisms. This study shows that the eDNA method utilizing the Next Generation Sequencing (NGS) approach are able to identify the protist more effectively, massively, and quickly compared to conventional methods based on morphological characteristics.